Signs of abnormal motor performance in preschool children - Martina Šlachtová; Kateřina Neumannová; Dagmar Dupalová (Palacky University, 2013)
BACKGROUND: The determination of the level of motor development should be a common part of examinations performed by paediatricians, physiotherapists and also teachers. The importance has been increasing because of the prevalence of developmental coordination disorder. OBJECTIVE: The aim of the study was to find the differences in performance of the selected motor tasks of gross motor function in preschoolers on both quantitative and qualitative parameters. METHODS: In the study 261 children were included, boys and girls aged 4–6 years (the average age 5.4 years) attending regular kindergartens. We used motor tasks of standing on one leg and hopping. Significant differences in quantitative parameters were assessed by two-way ANOVA in Statistica (version 9) software. Relative frequency of characters in qualitative parameters was assessed by the test of the difference between two proportions. RESULTS: Significant differences between the age groups appeared in the quantitative parameters comparing 4 and 5 year old children and 4 and 6 year old children. Regardless of gender there were no differences between 5 year and 6 year old children. Overall, the girls mastered the tasks of the test better than the boys in the quantitative parameters of evaluation. From the evaluation of the quality of motor performance the most frequently reached performance in the tasks of the test has been described (relative frequency of characters). Significantly different motor performance from most children of the sample was observed particularly in the associated movements of limbs or trunk and face, showing for a reduced ability of selective relaxation at higher demands of the movement task. CONCLUSIONS: The different motor performance in observed parameters, showing for a reduced ability of selective relaxation, could be regarded as signs of abnormal motor performance in that age category.